Penggabungan Mebel Multifungsi dengan Alat Musik Xylophone untuk Anak Sekolah Minggu di Surabaya - Govy Laurens; Adi Santosa; dody wondo (Intra, 2015)
Sunday School in a Catholic Church is known as BIAK (Bina Iman Anak Katolik) which consisted of all kids from the local parish who are willing to join, to play and to learn about Christ and Catholic Church teachings through the experienced teachers each week. The practice of Sunday School is not fully done in the Church building because of the enormous amount of the participants, which makes the participants are divided into several groups based on their living area. This division system makes some Sunday Schools are held in the residence of the people and leads into a problem of the limited area due to a shifted space function. Even the Sunday School which is held in the Church building also has a common problem. Those problems lead into an idea to make a multifunction furniture which are simple, flexible, and ease the process of Sunday School. This multifunction furniture is combined with the xylophone musical instrument to increase the spirit of the kids in singing and praising God, also to increase the kids ability to play music. The design of this multifunction  furniture includes the site survey with the area measuring process during the Sunday School, the kids anthropometrical measuring, the problem analysis during the event process, interview with the organizing committee, the data collection, literature study, programming, revision, a mock-up with the scale of 1:5 and ended with a 1:1 scaled real application which will be produced in 1 set multifunction furniture including its designed supportive elements.